1999
DOI: 10.1103/physrevb.59.77
|View full text |Cite
|
Sign up to set email alerts
|

Colossal resistive relaxation effects in aPr0.67Ca0.33MnO3

Abstract: We report here on an experimental study of slow thermal relaxation effects from the metastable metallicferromagnetic phase to the insulating one in a charge-ordered manganese oxide, Pr 0.67 Ca 0.33 MnO 3 . The metalinsulator transition is evidenced by an abrupt jump of the resistivity by several orders of magnitude at a well-defined time while there is no apparent singularity in the magnetization relaxation. This supports the view of a percolative behavior of current transport. The magnetic relaxation is discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
76
1
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(80 citation statements)
references
References 23 publications
2
76
1
1
Order By: Relevance
“…26,34,35 Such PS as well as the presence of the disorder commonly seen in thin films using MgO substrates, produces a finite peak structure as a result of the shifting of the Drude peak centered at ω = 0. Our samples show the ferromagnetic order at low-temperature; there is a significant hysteresis loop in M − H curve at 30 K with a coercive force of ∼ 500 Oe (Figs.…”
mentioning
confidence: 99%
“…26,34,35 Such PS as well as the presence of the disorder commonly seen in thin films using MgO substrates, produces a finite peak structure as a result of the shifting of the Drude peak centered at ω = 0. Our samples show the ferromagnetic order at low-temperature; there is a significant hysteresis loop in M − H curve at 30 K with a coercive force of ∼ 500 Oe (Figs.…”
mentioning
confidence: 99%
“…Insulator-metal transition in title compound can be induced by magnetic field 7 , electric current 10 , pressure 11 or X-rays 12 . These and other studies 13,14,15 converged around the idea of phase separation involving ferromagnetic metallic droplets coalescing and enabling the current percolation through the insulating matrix. The origin of phase separation lies in existence of structural inhomogeneities (clusters) associated with charge ordering 16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…The CO state is stabilized by an antiferromagnetic (AFM) ground state while that of the CD state is ferromagnetic (FM). [5][6][7] Moreover, many experiments have shown that the CO state is unstable under a variety of external perturbations including magnetic field, [8][9][10] temperature, external and chemical pressure 11 (i.e. degree of cation/anion doping), x-ray 12 and electron 13 irradiation.…”
Section: Iintroductionmentioning
confidence: 99%